New Therapies for Advanced Thyroid Cancer - Laha, Diprajan; Nilubol, Naris; Boufraqech, Myriem (Frontiers in Endocrinology, 2020)
Thyroid cancer is the most common endocrine cancer. The discovery of new biomarkers for thyroid cancer has significantly improved the understanding of the molecular pathogenesis of thyroid cancer, thus allowing more personalized treatments for patients with thyroid cancer. Most of the recently discovered targeted therapies inhibit the known oncogenic mechanisms in thyroid cancer initiation and progression such as MAPK pathway, PI3K/Akt-mTOR pathways, or VEGF. Despite the significant advances in molecular testing and the discoveries of new and promising therapeutics, effective treatments for advanced and metastatic, iodine-refractory thyroid cancer are still lacking. Here, we aim to summarize the current understanding of the genetic alterations and the dysregulated pathways in thyroid cancer and to discuss the most recent targeted therapies and immunotherapy for advanced thyroid cancer with a promising anti-tumor activity and clinical benefit.